2023
DOI: 10.1021/acsnano.2c12448
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitecture-Integrated Hydrogel Systems toward Therapeutic Applications

Abstract: Hydrogels, as one of the most feasible soft biomaterials, have gained considerable attention in therapeutic applications by virtue of their tunable properties including superior patient compliance, good biocompatibility and biodegradation, and high cargo-loading efficiency. However, hydrogel application is still limited by some challenges like inefficient encapsulation, easy leakage of loaded cargoes, and the lack of controllability. Recently, nanoarchitecture-integrated hydrogel systems were found to be thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 141 publications
(303 reference statements)
0
12
0
Order By: Relevance
“…Hydrogels offer several advantages for postoperative treatment, including cavity filling, tissue reconstruction promotion, sustained drug release, and prolonged immune response stimulation. , Previous studies have demonstrated the successful applications of hydrogel-formulated chemotherapeutics, tumor vaccines, and immunotherapeutics via local intracavitary administration to promote tumor regression and prevent tumor metastasis/recurrence. For instance, an oligopeptide-based in situ gelling formulation can rapidly form a gel network and provide sustained drug release for stimulating tumoricidal immunity, enabling effective inhibition of residual tumor cells and relapse prevention of malignant glioma recurrence after resection. , A thermosensitive hydrogel encapsulating a BRD4 inhibitor and indocyanine green-loaded tumor cells was employed as a personalized tumor vaccine for in situ immune activation at the surgical tumor site under laser irradiation . Indeed, hydrogels loading immune-activating drugs have been recognized as an excellent platform to generate in situ tumor antigens for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels offer several advantages for postoperative treatment, including cavity filling, tissue reconstruction promotion, sustained drug release, and prolonged immune response stimulation. , Previous studies have demonstrated the successful applications of hydrogel-formulated chemotherapeutics, tumor vaccines, and immunotherapeutics via local intracavitary administration to promote tumor regression and prevent tumor metastasis/recurrence. For instance, an oligopeptide-based in situ gelling formulation can rapidly form a gel network and provide sustained drug release for stimulating tumoricidal immunity, enabling effective inhibition of residual tumor cells and relapse prevention of malignant glioma recurrence after resection. , A thermosensitive hydrogel encapsulating a BRD4 inhibitor and indocyanine green-loaded tumor cells was employed as a personalized tumor vaccine for in situ immune activation at the surgical tumor site under laser irradiation . Indeed, hydrogels loading immune-activating drugs have been recognized as an excellent platform to generate in situ tumor antigens for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This is a challenge for traditional hydrogels due to their innate hydrophilicity. Therefore, such composite hydrogels provide an additional control knob to tailor release kinetics, bioavailability, and biodistribution. , In this respect, metal–organic frameworks (MOFs) offer much potential as an additive material in hydrogel depots to modulate drug release: their high porosities have allowed record-breaking drug loadings to be achieved, while their ease of bottom-up design allows their structures to be tailored for the shape, size, and chemical functionality of drug molecules. Indeed, MOF-hydrogel composites have gained considerable interest as a hybrid material in the past decade as the high water content, tissue mimicry, and biocompatibility of hydrogels facilitate the facile delivery of MOF in the body, as well as enhance the chemical and colloidal stability of the MOF additives. , Despite these advantages, the chemical-cross-linked nature of many polymeric hydrogels make them structurally rigid and difficult to administer as a drug depot. This drawback has stimulated the development of temperature-responsive hydrogels, otherwise known as thermogels, which can undergo reversible and spontaneous sol–gel transition when warmed. Unlike chemically cross-linked gels, thermogels gelate through the hierarchical supramolecular self-assembly of their constituent amphiphilic polymers without the need for additional chemical cross-linkers, driven largely by the hydrophobic effect in water.…”
Section: Introductionmentioning
confidence: 99%
“…By varying the structure and chemical composition of the internal polymer network, it is possible to control the NG’s amphiphilicity, , diffusion properties, responsiveness, and degradability . In biomedical applications, this allows tailoring of the NG's properties to very specific needs. , For example, as carriers in drug delivery, their internal structure can be optimized toward drug encapsulation and fine-tuning of specific triggered drug release profiles. In addition, their external surface also has a large influence on their interactions with biological systems. Dangling hydrophilic chains on the NG's surface can significantly lower (or select) protein adsorption from biological environments. , This effect can increase the NG’s stability in biological media as well as its circulation time in the body, reducing the immune response, and interactions with biological barriers can be determined .…”
Section: Introductionmentioning
confidence: 99%